ANALISIS HUKUM PENANGGULANGAN TINDAK PIDANA PENGGARAPAN LIAR DI PTPN III KEBUN BANGUN - Sutomo, Ibnu Syahputra; Yamin, Muhammad; Ekaputra, M. (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The problem of illegal cultivation on State-Owned Enterprise (BUMN) plantations that occurs at PT Perkebunan Nusantara III (PTPN III) Persero Kebun Bangun is not just a regional problem, but should be a national problem, a national and state problem, because the problem of illegal cultivation occurs in throughout Indonesia. The formulation of the problem in this thesis research is how to regulate positive law regarding criminal acts of illegal cultivation at PTPN III Kebun Bangun, what is the purpose of punishing criminal acts of illegal cultivation at PTPN III Kebun Bangun, how to deal with criminal acts of illegal cultivation at PTPN III Kebun Bangun. The research method used is a normative legal research method with descriptive analytical research characteristics, with a statutory statute approach, a conceptual approach, a historical legal approach, a historical legal approach, a comparative comparative approach, and a case approach. Primary, secondary and tertiary data sources, using library research techniques and document data collection are then analyzed qualitatively. It is necessary to increase the capacity of law enforcement officials in dealing with the problem of criminal acts of illegal cultivation.Keywords: Prevention, Crime, Illegal Cultivation, PTPN III Abstrak: Permasalahan dalam Penggarapan liar di perkebunan Badan Usaha Milik Negara (BUMN) yang terjadi pada PT Perkebunan Nusantara III (PTPN III) Persero Kebun Bangun bukan sekedar merupakan Masalah daerah, namun seharusya menjadi masalah nasional, masalah bangsa dan Negara, karena masalah penggarapan liar terjadi di seluruh wilayah Indonesia. Rumusan masalah dalam penelitian tesis ini adalah bagaimana pengaturan hukum positif terhadap tindak pidana penggarapan liar di di PTPN III Kebun Bangun, apa tujuan pemidanaan terhadap tindak pidana penggarapan liar di PTPN III Kebun Bangun, bagaimana penanggulangan tindak pidana penggarapan liar di PTPN III Kebun Bangun. Metode penelitian yang digunakan adalah metode penelitian hukum normatif dengan sifat penelitian deskriptif analisis, dengan pendekatan perundang-undangan statute approach, pendekatan konseptual conceptual approach, pendekatan sejarah hukum historical approach, pendekatan perbandingan comparative approach, dan pendekatan kasus case approach. Sumber data primer, sekunder dan tersier, dengan teknik penelitian kepustakaan (library research) dan pengumpulan data dokumen kemudian dianalisis secara kualitatif. Perlu dilakukan peningkatan kapasitas aparat penegak hukum dalam menghadapi masalah tindak pidana penggarapan liar ini.   Kata kunci: Penanggulangan, Tindak Pidana, Pengarapan Liar, PTPN III